2017
DOI: 10.1002/chem.201604517
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Activity and Thermodynamic Stability of Biliverdin IXβ Reductase Are Maintained by an Active Site Serine

Abstract: Biliverdin reductase IXβ (BLVRB) is a crucial enzyme in heme metabolism. Recent studies in humans have identified a loss-of-function mutation (Ser111Leu) that unmasks a fundamentally important role in hematopoiesis. We have applied experimental and thermodynamic modeling studies to provide further insight into role of the cofactor in substrate accessibility and protein folding properties regulating BLVRB catalytic mechanisms. Site-directed mutagenesis with molecular dynamic (MD) simulations establish the criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 75 publications
3
11
0
Order By: Relevance
“…5c). This is consistent with previous kinetics studies that also indicated a weaker coenzyme affinity [15]. The difference in coenzyme binding affinity would not be expected to significantly affect substrate turnover, which is collected at concentrations significantly higher than the K D of either the wild type or R78A mutant.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…5c). This is consistent with previous kinetics studies that also indicated a weaker coenzyme affinity [15]. The difference in coenzyme binding affinity would not be expected to significantly affect substrate turnover, which is collected at concentrations significantly higher than the K D of either the wild type or R78A mutant.…”
Section: Resultssupporting
confidence: 91%
“…For example, some of the largest CSPs induced by the coenzyme include residues 72–87 that are immediately within the BLVRB active site and the adjacent region of residues 34–39. This is consistent with a recent study that has shown that Arg35 is at least partially responsible for the selectivity of NADPH over NADH, as its side chain forms a direct interaction with the phosphate of the coenzyme [15]. Although in the absence of an apo BLVRB structure, it is difficult to deduce whether CSPs due to coenzyme binding are localized to side chain rearrangements or larger secondary structure rearrangements, it is worth noting that coenzyme binding to BLVRB induces higher CSPs than those previously reported for coenzyme binding to DHFR [23].…”
Section: Discussionsupporting
confidence: 93%
“…Attempts to obtain an experimental structure of the BLVRB-NADP ϩ -NSC130813 complex have been hampered by the low aqueous solubility of the ligand, although crystal structures of the xanthene-based inhibitors erythrosin extra bluish and phloxine B were solvable. Structures were nearly identical to ligand-free BLVRB (22), with ligands found within the ample BLVRB-binding site adjacent to the nicotinamide moiety of the cofactor and bordered by the flexible loops 80, 120, and the N-terminal half of the helix ␣E (27). Although erythrosin extra bluish and phloxine B bind less deeply than FMN or lumichrome into the BLVRB active site, both compounds interact with the side chain of Ser-111, a residue previously identified as critical for maintenance of the enzymatic active site (27) and cellular reductase functions that maintain redox balance and antioxidant handling in hematopoietic cells (26).…”
Section: Discussionmentioning
confidence: 85%
“…Structures were nearly identical to ligand-free BLVRB (22), with ligands found within the ample BLVRB-binding site adjacent to the nicotinamide moiety of the cofactor and bordered by the flexible loops 80, 120, and the N-terminal half of the helix ␣E (27). Although erythrosin extra bluish and phloxine B bind less deeply than FMN or lumichrome into the BLVRB active site, both compounds interact with the side chain of Ser-111, a residue previously identified as critical for maintenance of the enzymatic active site (27) and cellular reductase functions that maintain redox balance and antioxidant handling in hematopoietic cells (26). Consistent with what is observed in the crystal structures for phloxine B-and erythrosin-bound BLVRB, the halogen located on the tricyclic hydrocarbon of NSC130813 and NSC12516 is predicted to be in close proximity to Ser-111 (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation